2015
DOI: 10.1097/qad.0000000000000668
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and child psychological outcomes of HIV disclosure to young children in rural South Africa

Abstract: Amagugu led to improvements in mothers' and children's mental health and parenting stress, irrespective of disclosure level, suggesting general nonspecific positive effects on family relationships. Findings require validation in a randomized control trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 68 publications
2
45
0
Order By: Relevance
“…In the evaluation, we also demonstrated improvements in maternal and child mental health, with the intervention significantly reducing parenting stress, and children showing less emotional and behavioral difficulties post-intervention (25, 26). …”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…In the evaluation, we also demonstrated improvements in maternal and child mental health, with the intervention significantly reducing parenting stress, and children showing less emotional and behavioral difficulties post-intervention (25, 26). …”
Section: Resultsmentioning
confidence: 69%
“…Avoidant coping strategies include distraction, denial, escape, distancing, and self-blame, with mothers commonly coping with HIV by distancing themselves from it (32). By not disclosing, which is commonly reported in the HIV literature (18, 33, 34), the mother is practicing a form of avoidant coping, which is often motivated by a desire to safeguard children from psychological distress (26), or concerns about stigma and fear that the child may disclose to others (13, 35). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the paucity of literature describing the impact of disclosure of a child's perinatal HIV/ARV exposure, several studies suggest positive effects on family relationships when disclosure of maternal HIV status to children occurs [11,27,28]. The Amagugu study in South Africa reported significant reduction in parental stress and child emotional/behavioural problems after an intervention to aid in disclosure of maternal HIV status [27].…”
Section: Discussionmentioning
confidence: 99%